Anchoring-and-Adjustment During Affect Inferences - Yik, Michelle; Wong, Kin Fai Ellick; Zeng, Kevin J. (Frontiers in Psychology, 2019)
People can easily infer the thoughts and feelings of others from brief descriptions of scenarios. But how do they arrive at these inferences? Three studies tested how, through anchoring-and-adjustment, people used semantic and numerical anchors in inferring emotions from scenario descriptions. We showed that in a between-subject design, people’s emotion inference was biased towards anchoring information (Studies 1 and 2). People made fewer adjustments (anchoring increased) under time pressure in the high anchor but not the low anchor condition (Study 3). When inferring emotions from scenario descriptions, not only did people integrate their inference with the context, they adjusted away from initial anchors provided by experimenters. However, time pressure discouraged people from making adequate adjustments.